The Maine Memory Network: Re-Imagining the Dynamics and Potential of Local History - Bromage, Stephen (Maine Policy Review, 2015)
Stephen Bromage explores the Maine Historical Society’s experience creating, nurturing, and sustaining the Maine Memory Network (www.mainememory.net), a nationally recognized statewide digital museum. In particular, the article focuses on the opportunities that the digital humanities create to foster collaboration, to engage communities in the practice of history, and to collapse traditional geographic and institutional boundaries.
Keywords: Maine history; digital humanities; collaboration; community